A comparative study of exclusive breastfeeding between mothers of formal and informal sector workers in Ede north local government area, Osun State Nigeria - Comfort, Odewale O.; Obukohwo, Oyovwi M.; Oladapo, Jesutomi E.; Ademola, Omishakin M.; Joseph, Gregory Uchechukwu; Juliana, Elebiju O.; Faith, Falajiki Y.; Edet-Utan, Oluwakemi (International Journal Of Community Medicine And Public Health, 2023)
Background: Exclusive breastfeeding (EBF) is helpful in reducing infant morbidity and mortality throughout the first six months of life. However, despite aggressive marketing, just 13-36% of Nigeria infants under 6 months old are exclusively breastfed. Hence, this study was aimed to assess the knowledge, practice and factors affecting exclusive breastfeeding (EBF) among informal and formal sector workers in Ede north local government, Osun State. Methods: A descriptive study was conducted with 285 respondents from formal and informal sector workers with child(ren) aged 0-24 months. Results: Results showed a significant difference in knowledge and practice of exclusive breastfeeding between formal and informal sector workers. Factors affecting exclusive breastfeeding include lactation, job hindrances, and crèche availability. The practice of EBF was low among mothers in the formal sector, and the factors impacting its practice reported in this study may have substantial implications for breastfeeding intervention programs. Conclusions: As a result, attempts to promote EBF should target specific populations of informal sector women and areas where it is underutilized. Moreover, mothers must be supported. Furthermore, mothers should be encouraged to attend antenatal care where they will learn about the benefits of exclusive nursing to children under the age of six months, allowing them to make informed decisions on exclusive breastfeeding. The Nigerian government should ensure that the employment act’s maternity leave benefits are implemented in the informal sector, allowing women to practice EBF.